Cowpea viruses: effect of single and mixed infections on symptomatology and virus concentration - Taiwo, M.A.; Kareem, K.T.; Nsa, I.Y.; Hughes, J. (Springer, 2007)
Natural multiple viral infections of cultivated cowpeas have been reported in Nigeria. In this study, three Nigerian commercial cowpea cultivars ("Olo 11", "Oloyin" and "White") and two lines from the IITA (IT86D- 719 and TVU 76) were mechanically inoculated with Cowpea aphid-borne mosaic virus (CABMV), Bean southern mosaic virus (SBMV) and Cowpea mottle virus (CMeV) singly, as well asin all possible combinations at 10, 20 and 30 days after planting (DAP). Samples of leaves or stems were collected at 10, 20 and 30 days after inoculation (DAI) and analyzed for relative virus concentration by Enzyme-Linked Immunosrbent Assay. All the cultivars and lines {CVS/L} were susceptible to the viruses but the commercial CVS showed more severe symptoms and had relatively higher viral concentration. In single virus infections, CABMV which induced the most severe symptoms had absorbance values (at 405 nm) of 0.11 to 0.46 while SBMV and CMeV which induced moderate symptoms had virus titre of 0.74 to 1.99 and 0.11 to 0.90 respectively. Plants inoculated 10 DAP had significantly higher virus concentration than those inoculated 30 DAP. Inmixed infections involving CABMV (10 DAP) apical necrosis and death were observed in commercial cultivars "Olo 11" and "White". Enhancement of CMeV titers were observed in plants infected with CMeV + CABMV. Multiple viral infections of cowpeas may result in complete yield loss, hence, the availability of seeds of cultivars with a high level of multiple virus resistance is recommended as a means of control.